RETRACTED: A study on expression level and nutritional status of IGFBP-2 after left neck anastomosis combined with placement of feeding nutritional applicators carrying ^(125)I particles in the treatment of esophageal cancer - Zhan, Zhiqiang; Mei, Jiaqi; Zhou, Xiangwu; Jiang, Sicong; Li, Daojing; Wang, Xuefeng (Frontiers in Oncology, 2022)
Background: To explore the changes and significance of the expression level and nutritional status of human insulin-like growth factor binding protein-2 (IGFBP2) after the treatment of esophageal cancer with left neck anastomosis combined with placement of feeding nutritional applicators carrying ^(125)I particles. Methods: A total of 110 patients with esophageal cancer (observation group: left neck anastomosis combined with placement of feeding nutritional applicators carrying ^(125)I particles) and 100 healthy people (control group) were enrolled at the same period. Then enzyme-linked immunosorbent assay (ELISA) was carried out to detect level of IGFBP-2. Lymphocyte count and serum albumin were measured by immune analyzer and automatic protein analyzer to evaluate nutritional status. Logistic regression analysis was used to analyze the relationship between serum IGFBP-2, nutritional status and prognosis of esophageal cancer after combined treatment. Results: The albumin, lymphocyte absolute value and PNI detection value of the control group were lower than those of the observation group 1 month after treatment, and the difference was statistically significant compared with the control group. The detection value of IGFBP-2 in early patients before and after treatment was lower than that in middle and late patients, and the detection values of albumin, lymphocyte absolute value and PNI were higher than those in middle and late patients, the differences were statistically significant. Serum IGFBP-2 level was negatively correlated with PNI, and albumin and lymphocyte absolute value were positively correlated with PNI. The detection value of IGFBP-2 in patients with good prognosis was significantly lower than that in patients with poor prognosis, and the detection values of albumin, lymphocyte absolute value and PNI were significantly higher than those in patients with poor prognosis. The AUC (0.887,95 % CI: 0.799-0.975) of IGFBP-2, albumin, lymphocyte absolute value and PNI in predicting poor prognosis of esophageal cancer was the largest, and the sensitivity and specificity were 94.12 % and 92.47 %, respectively. Conclusions: Left neck anastomosis combined with ^(125)I particle application nutritional tube is helpful for the decrease of serum IGFBP-2 and the increase of various nutritional status indicators, which is beneficial for the improvement of the patient's condition.